How The Scoundrel Seduces - Jeffries, Sabrina (New York Pocket Books, 2014)
While trying to ensure that his half-brother George can never ruin his life again, investigator Tristan Bonnaud, one of the Dukes Men, is hired by Lady Zoe Keane to find a gypsy woman who knows all of her familys secrets.
"Pocket books romance"--Spine.
Keywords: Nobility -- England; Fiction; Aristocracy (Social class) -- Fiction; Romanies -- Fiction; Family secrets -- Fiction; Romance fiction; Regency fiction